S. N. Bernstein Type Estimations in the Mean on the Curves in a Complex Plane - J. I. Mamedkhanov; I. B. Dadashova (Abstract and Applied Analysis)
The present paper discusses in the metric Lp S. N. Bernstein type inequalities of the most general kind on very general accessible classes of curves in a complex plane. The obtained estimations, generally speaking, are not improvable.